A Workplace Mindfulness Intervention May Be Associated With Improved Psychological Well-Being and Productivity. A Preliminary Field Study in a Company Setting - Kersemaekers, Wendy; Rupprecht, Silke; Wittmann, Marc; Tamdjidi, Chris; Falke, Pia; Donders, Rogier; Speckens, Anne; Kohls, Niko (Frontiers in Psychology, 2018)
Abstract Background: Mindfulness trainings are increasingly offered in workplace environments in order to improve health and productivity. Whilst promising, there is limited research on the effectiveness of mindfulness interventions in workplace settings. Objective: To examine the feasibility and effectiveness of a Workplace Mindfulness Training (WMT) in terms of burnout, psychological well-being and organizational and team climate and performance. Methods: This is a preliminary field study in four companies. Self-report questionnaires were administered up to a month before, at start of, and right at the end of the WMT, resulting in a pre-intervention and an intervention period. There was no separate control group. A total of 425 participants completed the surveys on the different time points. Linear mixed model analyses were used to analyze the data. Results: When comparing the intervention period with the pre-intervention period, significantly greater improvements were found in measures of burnout (mean difference=0.3, p<0.001), perceived stress (mean difference=-0.2, p<0.001), mindfulness (mean difference =1.0 for the Freiburg Mindfulness Inventory (FMI) and 0.8 for the Mindfulness Attention Awareness Scale (MAAS), both p<0.001), and well-being (mean difference=0.4, p<0.001). Additionally, greater increases in team climate, organizational climate and personal performance were reported during the intervention compared to the pre-intervention period with largest improvements in team cooperation (mean difference=0.3, p<0.001), productivity (mean difference=0.5, p<0.001), and stress (mean difference=-0.4, p<0.001). Effect sizes were large for mindfulness (d>0.8), moderate for well-being, burnout and perceived stress (d=0.5 - 0.8), and ranged from low to moderate for organizational and team climate and personal performance (d=0.2 - 0.8). Conclusion: These preliminary data suggest that compared to the pre-intervention period, the intervention period was associated with greater reductions in burnout and perceived stress, improvements in mindfulness, well-being, and increases in team and organisational climate and personal performance. Due to design limitations, no conclusions can be drawn on the extent to which the WMT or non-specific factors such as time have contributed to the findings. Further studies, preferably using randomized controlled designs with longer follow up periods are needed to evaluate whether the associations found can be attributed to the WMT and whether these sustain after the training.